Nano-antivirals: A comprehensive review - Hussain, Fayyaz Salih; Abro, Naveed Qasim; Ahmed, Naseer; Memon, Saima Q.; Memon, Najma (Frontiers in Nanotechnology, 2022)
Nanoparticles can be used as inhibitory agents against various microorganisms, including bacteria, algae, archaea, fungi, and a huge class of viruses. The mechanism of action includes inhibiting the function of the cell membrane/stopping the synthesis of the cell membrane, disturbing the transduction of energy, producing toxic reactive oxygen species (ROS), and inhibiting or reducing RNA and DNA production. Various nanomaterials, including different metallic, silicon, and carbon-based nanomaterials and nanoarchitectures, have been successfully used against different viruses. Recent research strongly agrees that these nanoarchitecture-based virucidal materials (nano-antivirals) have shown activity in the solid state. Therefore, they are very useful in the development of several products, such as fabric and high-touch surfaces. This review thoroughly and critically identifies recently developed nano-antivirals and their products, nano-antiviral deposition methods on various substrates, and possible mechanisms of action. By considering the commercial viability of nano-antivirals, recommendations are made to develop scalable and sustainable nano-antiviral products with contact-killing properties.